Development and test of an intra-vehicular network based on bluetooth low energy - Silva, Rita B. C. (2017)
This paper presents the development and test of an intra-vehicular system, based on Bluetooth Low Energy (BLE), designed to present to the driver, in real-time, information collected from multiple sensors distributed inside of the car, using an Android smartphone. The architecture of the implemented BLE network is composed by the smartphone, which has the role of central station, and two BLE modules (peripheral stations) based on the CC2540 system-on-chip, which collect relevant sensor information from the battery system and the traction system of an electric car. Results based on an experimental performance evaluation of the wireless network show that the network is able to satisfy the application requirements, as long as the network parameters are properly configured taking into account the peculiarities of the BLE data transfer modes and the limitations of the BLE platform.